2019
DOI: 10.33893/fer.18.1.532
|View full text |Cite
|
Sign up to set email alerts
|

Brave New Digital World? – Financial Technology and the Power of Information

Abstract: In this paper we focus on the development of FinTech, how is it evaluated and managed in selected areas, in the European Union, in China and in Hungary. Some of the pertinent questions in this field are the following: How can regulators keep up with the rapid pace of development? Can regulation be based on a precise definition and can a level playing field be ensured between traditional banks and FinTech start-ups? What are the risks? How can they be handled by supervision and regulation? We can conclude that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The restrictions led people to switch to remote working or learning schemes. This, in turn, resulted in the revaluation of digital achievements and contributed to the importance of broadband internet access in various spheres (e.g., shopping, managing finances, entertainment) (Kerényi and Müller, 2019). Other authors also revealed that the spread of coronaviruses has fuelled the growth of e-commerce as a platform to conduct businesses between retailers and consumers or business-to-business (Karácsony, 2020; Kitukutha et al, 2021).…”
Section: /646mentioning
confidence: 99%
“…The restrictions led people to switch to remote working or learning schemes. This, in turn, resulted in the revaluation of digital achievements and contributed to the importance of broadband internet access in various spheres (e.g., shopping, managing finances, entertainment) (Kerényi and Müller, 2019). Other authors also revealed that the spread of coronaviruses has fuelled the growth of e-commerce as a platform to conduct businesses between retailers and consumers or business-to-business (Karácsony, 2020; Kitukutha et al, 2021).…”
Section: /646mentioning
confidence: 99%
“…Digitization and its phenomena, both convergence and transcoding, have brought about a new theoretical change, which also has the main characteristic of rendering other traditional management modes completely obsolete [46,47]. One of these changes refers to the collapse of traditional borders that separated communicational and informational activity (sender, message and receiver) into psychosocial dimensions [32,48,49]. This division has disappeared and its limits are blurred in the phenomena of the new technological means.…”
Section: Frameworkmentioning
confidence: 99%
“…In this fourth period, the fintech phenomenon formally implies a paradigm shift that has revolutionised the financial sector, and the challenges it poses are analysed [32,146].…”
Section: Evolution Of Abstractmentioning
confidence: 99%
“…From the end of April 2020, besides Budapest and Pest county, an increasing number of new infected cases was detected predominantly in the western counties (Fejér, Komárom-Esztergom, Veszprém, Zala), and from the beginning of July, the daily number of new infections was on the rise in the eastern part of the country, in Borsod-Abaúj-Zemplén and Csongrád-Csanád and Hajdú-Bihar counties, respectively. If we look at the spatial diffusion of the pandemic in the first half of 2020, we can see territorial (Budapest, Pest county) and institutional (hospitals, nursing homes) hotspots (Kemenesi et al, 2020). The short-term health consequences of the new coronavirus pandemic included the growing demand for the hospitalisation of infected patients: as the number of such patients grew, so did the risks of overburdening the health care system and the risks of the country facing capacity shortages.…”
Section: The Main Features Of the First Wave Of The New Coronavirus Pmentioning
confidence: 99%